2022
DOI: 10.3389/fnagi.2022.885680
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Patatin-Like Phospholipase Domain-Containing Protein 6 Gene Contributes to the Risk of Intracranial Aneurysm in Males

Abstract: Objective: This study is aimed to investigate the contribution of patatin-like phospholipase domain-containing protein 6 (PNPLA6) DNA methylation to the risk of intracranial aneurysm (IA) in the Han Chinese population.Methods: A total of 96 age- and sex-matched participants were recruited to evaluate PNPLA6 methylation via bisulfite pyrosequencing. The PNPLA6 mRNA expression in the plasma was determined using real-time quantitative reverse transcription-polymerase chain reaction. Human primary artery smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…YAP forward primer, 5′-ACAATGACGACCAATAGCTCAGAT-3′; YAP reverse primer, 5′-AACGGTTCTGCTGTGAGGG-3′. The sequence of the internal reference gene ACTB and the calculation method of mRNA expression have been described in our previous study [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP forward primer, 5′-ACAATGACGACCAATAGCTCAGAT-3′; YAP reverse primer, 5′-AACGGTTCTGCTGTGAGGG-3′. The sequence of the internal reference gene ACTB and the calculation method of mRNA expression have been described in our previous study [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maimaiti et al used novel bioinformatics methods, including transcriptomics analysis, machine learning algorithms, genome-wide association studies (GWAS), Mendelian randomization (MR), and summary data-based Mendelian randomization (SMR), to demonstrate the association between DNA methylation-related genes DNMT3A, MBD2, DNMT1 , and DNMT3B and IA susceptibility [ 12 ]. Zhou et al found that DNA methylation levels are associated with the risk of IA in Chinese males [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increased methylation at phospholipase domain-containing protein 6 ( PNPLA6 ), leading to its consequent reduction in mRNA expression, was found to affect intracranial aneurysm development [ 73 ].…”
Section: -Omics Application In Taa Studiesmentioning
confidence: 99%
“…The primer sequences were as follows: MTA1 forward primer, 5 -TACCTGGAGCGGGAGGATTTCTT-3 ; and reverse primer, 5 -GCTTGTCTGTGAGTGGGTTGTGC-3 . ACTB was used as an internal reference [24], with the forward primer being 5 -AGCACAGAGCCTCGCCTT-3 and the reverse primer being 5 -CATCATCCATGGTGAGCTGG-3 . The 2 − Ct method was used to calculate mRNA expression.…”
Section: Quantitative Real-time Polymerase Chain Reactions (Rt-qpcr)mentioning
confidence: 99%